2021
DOI: 10.1097/qai.0000000000002620
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Interruptions to HIV Prevention and Treatment Services Associated With COVID-19 for Gay, Bisexual, and Other Men Who Have Sex With Men in 20 Countries

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 28 publications
8
59
0
Order By: Relevance
“…This experience is not unique to KPs in India. Emerging data on the impact of COVID‐19 among MSM in various sites illustrate how HIV antibody testing has been harder to access [ 13 , 15 , 16 ], which was also seen in the United States, as the pandemic caused interruptions and declines in HIV/STI testing access [ 17 ]. HIV programs globally saw fewer clients living with HIV complete HIV RNA testing over the initial months of COVID‐19 compared to pre‐pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This experience is not unique to KPs in India. Emerging data on the impact of COVID‐19 among MSM in various sites illustrate how HIV antibody testing has been harder to access [ 13 , 15 , 16 ], which was also seen in the United States, as the pandemic caused interruptions and declines in HIV/STI testing access [ 17 ]. HIV programs globally saw fewer clients living with HIV complete HIV RNA testing over the initial months of COVID‐19 compared to pre‐pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large online study of men who have sex with men (MSM) ( n = 2,732) from 103 countries reported that 33% of participants living with HIV lost access to HIV providers due to COVID-19, and nearly one-fifth who were taking antiretroviral therapy reported challenges accessing medication ( Santos et al, 2020 ). In another survey of MSM ( n = 10,654) in 20 countries using geosocial networking apps, interruptions to HIV prevention services were common (e.g., 56% for pre-exposure prophylaxis, 38–55% for HIV testing) and significantly associated with the stringency of national restrictions related to COVID-19 ( Rao et al, 2021 ). LGBT persons may also avoid COVID-19 testing or emergency care due to pre-existing fears of mistreatment in health facilities ( Bauer et al, 2014 ).…”
Section: How Are Gender and Sexual Minorities Impacted By Covid-19?mentioning
confidence: 99%
“…A growing body of literature describes global interruptions to prescriptions for diseases like HIV, increases in depression, and significant losses of job, insurance, and food security as a result of COVID-19 [7][8][9][10][11]. However, recent research has demonstrated that these effects disproportionately burden groups that are already marginalized.…”
Section: Introductionmentioning
confidence: 99%